Social Perceptions of a Creative Person: Stereotypes and Prejudice of a Creative Student among German Adolescents - Zhang, Zhitian; Hopp, Manuel; Vialle, Wilma; Ziegler, Albert (Creativity Research Journal, 2020)
This study builds from the implicit theory of creative individuals to an understanding of the social perceptions of creative individuals. Stereotypes and prejudice about creative students were examined utilizing the self-developed stereotype and prejudice scales among German adolescents. The results indicate that German adolescents hold positive images of creative students, seeing them as competent, warm and popular. Their primary perception of a creative student was admiration, which could be predicted by their stereotypes. In addition, the gender and age effects on adolescents’ social perception were examined. The results show that boys and girls tend to expect the creative student to be the same gender as themselves; and the ratings of stereotype and prejudice in the pre-teens group were significantly higher than in the teens group. These findings provide a refined image of creative individuals from a social perception perspective and partially explain the observed variations due to gender and age factors.
CRIS-Team Scopus Importer:2020-10-30